Monitoring system for arthritis patients - flex sensor approach - Sharavanan Rajasagaran (Nanyang Technological University, 2022)
Technological revolution has paved way to inventions that has been deemed impossible in the past. Its impact is seen in our daily lives. From enabling instant communications, to high-speed computations that surpass what humans are capable of, technology has greatly improved the quality of human lives. This project aims to implement one such idea that can be useful in the medical industry. Arthritis is a very common illness experienced as people age. Although this condition does not have a cure, there are multiple treatments available that can help patients manage the pain and limit the progress of its deterioration. But it is essential to properly monitor the progress of this condition to craft an effective treatment customized to individual patients. Although radiography can accurately provide healthcare workers with the severity of arthritis symptoms, it may not be the best possible solution as radiography can bring about unwanted side effects. It is also not practical as a daily monitoring aid. Hence, this project aims to use Flex sensors to monitor the progress of arthritis condition in the hand joints and provide healthcare workers and patients with relevant data. This data can be used to implement effective treatment plans for patients.